2019
DOI: 10.1111/flan.12425
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the pedagogical affordances of a collaborative board game in a dual language immersion classroom

Abstract: In this study, we present an educational board game designed to promote both mathematics and Chinese language learning. We use text‐mining techniques to analyze dialog by 40 students, in six groups playing a board game in a dual language immersion context. Our findings provide evidence to support past claims and arguments that play and specifically play within board games can provide a learning environment in which students can experiment with concepts and language without fear of failure. In our study, we not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Of the 93 chapters, 80% (n = 74) feature the use of analog games (card, dice, communication games) and only 20% (n = 19) feature digital games. Yet, in the last 20 years, there are only a handful of studies exploring the use of analog games for language learning (e.g., Luk, 2013;F. Poole et al, 2019;Smith, 2006;York, 2020a) compared to numerous systematic reviews on digital games identified above.…”
Section: Dgbll Is Not Teaching-focusedmentioning
confidence: 99%
“…Of the 93 chapters, 80% (n = 74) feature the use of analog games (card, dice, communication games) and only 20% (n = 19) feature digital games. Yet, in the last 20 years, there are only a handful of studies exploring the use of analog games for language learning (e.g., Luk, 2013;F. Poole et al, 2019;Smith, 2006;York, 2020a) compared to numerous systematic reviews on digital games identified above.…”
Section: Dgbll Is Not Teaching-focusedmentioning
confidence: 99%
“…Second, this study helps to expand the media variety and language learning potential through the use of the AR‐enhanced board game in the broader research field of game‐based learning. The innovative merger of image‐based AR and physical board gaming pieces into a hybrid form of mediation likely encouraged face‐to‐face interaction of meaningful language use that was highly valued in physical board games (e.g., student players explaining their thinking to others in the present study), while also providing immediate access to virtual content and scaffolding by taking advantage of AR technology (Godwin‐Jones, 2016; Poole et al, 2019). The mechanics (e.g., grid movement, card drawing, and set collection) of the developed game were additional stimuli to better engage the experimental group in the game‐based vocabulary learning process, compared to the relatively simple question‐and‐answer mechanism involved in the traditional puzzles for the comparison group.…”
Section: Discussionmentioning
confidence: 99%
“…Given that games are widely appealing, they provide many affective benefits for active learner engagement, such as motivation (Wu, 2018), enjoyment (Hung & Young, 2015), and satisfaction (Wu, 2021), all of which in turn lead to improved acquisition of words. Additional benefits of learning vocabulary by playing games are, for example, providing an interaction context for players/learners to use the lexical item for communication with others (Peterson, 2016), offering peer support to foster knowledge construction via a collaboration‐based mechanism (Poole et al, 2019), and stimulating learners' willingness to actively overcome challenges via a competition‐based mechanism (Yang et al, 2020). Along the same line, in Tsai and Tsai's (2018) meta‐analysis of 26 empirical studies, a large overall effect size was found for research that exposed language learners to game‐based vocabulary learning environments as compared to non‐game‐related ones.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The games also provided a platform for learners to use their L1 productively to engage in meta-talk and learn new LX. Poole et al (2019) conducted a study with English speakers learning Chinese, using a board game designed to promote math and Chinese development. Results showed that the board game was an effective medium for LX usage and development because learners could use their LX communicatively and engage in peer learning.…”
Section: Bowyer: Developing Intercultural Connections and Language Competence With Board Gamesmentioning
confidence: 99%